Integration Model of Sharia Accounting and Financial Technology (Fintech) for MSMEs - Abdul Rachman Rika (Mabsya: Jurnal Manajemen Bisnis Syariah, 2026)
This study aims to examine the role of Islamic accounting, Islamic financial literacy, and digital readiness on the feasibility of MSME financing, by considering the mediating role of Islamic fintech usage intention, trust, and business sustainability. A quantitative approach was used through Partial Least Squares-based Structural Equation Modeling (PLS-SEM) analysis, with data collected from MSMEs using Islamic fintech services. Results show that most of the direct relationships between variables are statistically significant, especially the effect of Islamic accounting on intention and trust, and business sustainability on financing eligibility. Another important finding is the functioning of the mediation path, which suggests that intention and trust are important links in the chain of influence towards viable financing. However, the moderating interaction between literacy and digital readiness on Islamic accounting relationship was not significant. This study strengthens the Technology Acceptance Model (TAM) framework extended by Islamic ethical principles. The original contribution of this study lies in the integration of Islamic values in the financial technology adoption process as well as the establishment of an inclusive and sustainable Islamic financing ecosystem for MSMEs.